1940
DOI: 10.1063/1.1750625
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evidence for Hydrogen Bonds: Comparison of Proton-Attracting Properties of Liquids. II

Abstract: Forty-two different organic liquids are rated according to their proton-attracting power by comparing the strength of the hydrogen bonds which they form with heavy methyl alcohol. The classes of liquids studied are: aldehydes, ketones, esters, ethers and amines. The amount of perturbation which the different solvents cause in the OD vibrational band of the CH3OD is taken as a measure of the strength of the deuterium bridges formed with the CH3OD. The study is a continuation of a previous work in which twenty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1943
1943
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…The evidence of other workers (3,4) indicates that alkyl aryl ethers are considerably less basic than aromatic aldehydes and ketones. This difference should be even more pronounced where there is an electron-withdrawing forilly1 group para to the alkoxyl group as shown below:…”
Section: Ejects Of Meta and Para Substitution On Basicitymentioning
confidence: 73%
“…The evidence of other workers (3,4) indicates that alkyl aryl ethers are considerably less basic than aromatic aldehydes and ketones. This difference should be even more pronounced where there is an electron-withdrawing forilly1 group para to the alkoxyl group as shown below:…”
Section: Ejects Of Meta and Para Substitution On Basicitymentioning
confidence: 73%
“…•NH(CHah) i and that dipole-dipole forces, resonance stabiliza tion, and dispersion forces all contribute to the bridge strength. Spectro scopic studies (e.g., 136,137) have shown that -COOH >-CONH2 > OH are the most effective donor groups, -NH2 being considerably weaker ; and that the approximate potency sequence for acceptors is…”
Section: The Molecular Basis Of Main-pattern Selectivitymentioning
confidence: 99%
“…However, the general pattern of behavior of bromphthalein magenta and its salts can be interpreted satisfactorily from a consideration of the proton-affinity of the solvent, but not from a consideration of its dielectric constant. Gordy has pointed out that there is no correlation evident in the dipole moments of solvents and the strengths of the bonds formed with CH30D [79].…”
Section: Acid-base Reactions In Organic Solventsmentioning
confidence: 99%
“…In studying the deuteron-attracting properties of liquids by infrared pec troscopy, Gordy and his collaborators [78,79] measured the shift of the OD band of heavy methyl alcohol, CHaOD, or heavy water, DzO. Benzene was used as r eference solvent for CHaOD or D zO.…”
Section: Acid-base Reactions In Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation